Faktor-Faktor yang Mempengaruhi Kepatuhan Pengobatan pada Pasien Diabetes Mellitus Rawat Jalan di RSUD Sukoharjo - Yulianti, Tri; Anggraini, Lusi (Universitas Muhammadiyah Surakarta, 2020)
Diabetes mellitus is a chronic metabolic with high prevalence and it can increase the risk of the complications, if it not handled properly. Medication adherence is one of the determining factor to achive therapeutic outcome. This research aims to determine the affecting factors of adherence inÂ diabetes mellitus type 2 outpatient at RSUD Sukoharjo in 2020. This research type isÂ cross sectional with a purposive sampling technique. A total of 85 patients diabetes mellitus type 2 outpatient at RSUD Sukoharjo with inclusion criteria received OAD therapy (Oral Antidiabetic Drugs) or a combination of OAD with insulin for at least 1 month, recruited in this study. The data was collected from medical records and questionnaires. Adherence was measured by using the MARS 5 questionnaire (Medication Adherence Report Scale 5). Factors contributing to medication adherence was analyzed by using chi-square test. The results showed that 37 respondents (43.5%) were obedient. The significant factors of medication adherence are monthly income (p-value = 0.018 and OR = 2.887), Medication (p - value = 0.007 and OR = 3,551), the frequency of treatment (p-value = 0.006 and OR = 3,529) and blood glucose level (p-value = 0.006 and OR = 3,529).